The invisible wall : a love story that broke barriers - Bernstein, Harry, 1910- (New York : Ballantine Books, 2007)
In a memoir set on the eve of World War I, the author describes growing up in a working-class town in northern England, where Jews and Christians were strictly divided, and how his sister's love for a Christian boy broke down the invisible social barrier.
Keywords: Bernstein, Harry -- Childhood and youth; Bernstein, Harry -- Homes and haunts -- England -- Lancashire; Authors, American -- 21st century -- Biography; Jews -- England -- Biography; Lancashire (England) -- Social life and customs